2015
DOI: 10.1128/aac.05139-14
|View full text |Cite
|
Sign up to set email alerts
|

Enantiomers of Nifurtimox Do Not Exhibit Stereoselective Anti-Trypanosoma cruzi Activity, Toxicity, or Pharmacokinetic Properties

Abstract: e With the aim of improving the available drugs for the treatment of Chagas disease, individual enantiomers of nifurtimox were characterized. The results indicate that the enantiomers are equivalent in their in vitro activity against a panel of Trypanosoma cruzi strains; in vivo efficacy in a murine model of Chagas disease; in vitro toxicity and absorption, distribution, metabolism, and excretion characteristics; and in vivo pharmacokinetic properties. There is unlikely to be any therapeutic benefit of an indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“… 62 A study published in 2015 concluded that it was unlikely that a single enantiomer of nifurtimox would have a therapeutic advantage over the racemate ( 19 and 20 , Figure 10 ). 63 This conclusion was based on an observed lack of stereoselectivity in the toxicity, pharmacokinetics, and activity of nifurtimox against T. cruzi .…”
Section: Resultsmentioning
confidence: 99%
“… 62 A study published in 2015 concluded that it was unlikely that a single enantiomer of nifurtimox would have a therapeutic advantage over the racemate ( 19 and 20 , Figure 10 ). 63 This conclusion was based on an observed lack of stereoselectivity in the toxicity, pharmacokinetics, and activity of nifurtimox against T. cruzi .…”
Section: Resultsmentioning
confidence: 99%
“…The current chagas disease treatment, which has been in use for over 40 years, is centered on the nitro heterocyclic drugs nifurtimox and benznidazole (Figure 1), both of which exhibit trypanosomicidal action against all parasite forms. Nifurtimox is a racemic mixture which is as effective and safe as its individual enantiomers (Moraes et al., 2015). They are deemed far from optimal due to the adverse effects that can disrupt the therapeutic procedure and the low curative efficacy (Castro et al., 2006; Coura & de Castro, 2002; Jannin & Villa, 2007; Rocha et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of genetically unmodified parasites has always been an attractive pursuit, made available only recently due to technologic advancements. Such cell-based assays were developed by researchers at Institut Pasteur Korea and have met widespread use [15][16][17][18]. This assay employed the use of wild type parasites of T. cruzi infecting a non-modified cell line and the imaging of the resulting infection (in the amastigote stage) by high-content analysis (HCA) microscopy.…”
Section: Introductionmentioning
confidence: 99%